(untitled) (ASEAN Engineering Journal, 2012)
Technology transfer has become a common practice of countries and organizations to acquire technology. Aside from enabling less advanced countries or organizations to acquire technology for economic advancement, a significant advantage of technology transfer is that it enables advanced countries to outsource their internal Research and Development (R&D). Thus, technology transfer results in the symbiotic relationship among organizations and countries. Although technology transfer is not a novel undertaking, it still encounters challenges. One of these is the transfer of decision-making capabilities. Decision-making capabilities are needed to sustain and enable local development of the technology. However, these capabilities are difficult to transfer. For this, this research proposes the Iterative Methodology of Analysis and Synthesis of Technology Components. The combination of analysis and synthesis is aimed at addressing the need to break down (analyze) the technology to present it in a more understandable form and the necessity to put a story (synthesize) to the technology to ensure the understanding of the technology by the recipient. Moreover, the “iterative” characteristic is to make sure that there is feedback and agreement between the transferor and the recipient. To prove the validity of the Iterative Analysis and Synthesis Model that this research proposes, a case study was performed on a long-standing technology transfer partnership between a Japanese mother company and its Philippine subsidiary. This research has found that the case study applied a technology transfer methodology that is similar to the methodology being proposed by this research. More case studies have been and are being performed to further prove the validity of this research. However, in this paper, one case study is specifically described. Although the discussion of the results of the case study brief in this paper, i.e., the results of the case studies are more comprehensively discussed in another paper, the results of the initial case study show that, in many aspects, the proposed Iterative Analysis and Synthesis Methodology is in agreement with the methodology that brought success to the technology transfer participants in the initial case study described herein. In conclusion, this research believes that given the previous related research works, the discussions in this research and the case study performed, the proposed methodology is valid. Furthermore, because the proposed methodology has been similarly applied in an existing technology transfer undertaking and has been observed to yield positive results, the proposed methodology is to some extent, credible and confirmable.